2016
DOI: 10.5114/ceji.2016.60998
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled corticosteroids do not reduce initial high activity of matrix metalloproteinase (MMP)-9 in exhaled breath condensates of children with asthma exacerbation: a proof of concept study

Abstract: Inhaled corticosteroids (ICS) are the key component of asthma treatment. However, it is unclear whether they could control the activity and level of matrix metalloproteinase (MMP)-9, which is an important factor in asthma-associated inflammation and airway remodeling. Therefore, the aim of this proof of concept study was to analyze the influence of increased doses of ICS on MMP-9 in exhaled breath condensates (EBC) of patients with allergic asthma exacerbation. Apart from MMP-9, the assessment concerned select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 51 publications
0
9
0
1
Order By: Relevance
“…We have used 23 randomly selected samples of already deposited breath condensates, excessively collected during our recent projects, focused on children with severe (n ¼ 6) and mild asthma (n ¼ 8), respectively [5,6]. The control group comprised samples of breath condensates (n ¼ 9) from age-matched healthy individuals.…”
Section: Methodsmentioning
confidence: 99%
“…We have used 23 randomly selected samples of already deposited breath condensates, excessively collected during our recent projects, focused on children with severe (n ¼ 6) and mild asthma (n ¼ 8), respectively [5,6]. The control group comprised samples of breath condensates (n ¼ 9) from age-matched healthy individuals.…”
Section: Methodsmentioning
confidence: 99%
“…In an older study, Russell et al 11 reported that dexamethasone decreased the production of MMP -9 by BALF-derived alveolar macrophages from COPD patients. On the other hand, Grzela et al 21,41 found that ICSs do not decrease MMP -9 activity in EBC in asthma, either during prolonged treatment in patients with stable disease or during disease exacerbation. Nevertheless, these findings cannot be directly compared with our results, as they were observed in a different study population, that is, children with asthma.…”
Section: Matrix Metalloproteinase 9 Levels and Functional And Clinicamentioning
confidence: 99%
“…After treatment of the exacerbation (defined according to GINA guidelines), no differences were found between asthmatic and healthy children (29). The third study assessed the cytokines tumor necrosis factor (TNF) and IL-8, and a marker of airway remodeling [matrix metalloproteinase (MMP)-9] in EBC in a very small group ( n = 4) of children with an asthma exacerbation (30). After 4 weeks of increasing the ICS dose, the concentration of TNF in EBC significantly decreased (30).…”
Section: Findings From Longitudinal Studiesmentioning
confidence: 99%
“…The third study assessed the cytokines tumor necrosis factor (TNF) and IL-8, and a marker of airway remodeling [matrix metalloproteinase (MMP)-9] in EBC in a very small group ( n = 4) of children with an asthma exacerbation (30). After 4 weeks of increasing the ICS dose, the concentration of TNF in EBC significantly decreased (30). However, the concentration of MMP-9 did not change, and more importantly, IL-8 was below the detection limit in all children (30).…”
Section: Findings From Longitudinal Studiesmentioning
confidence: 99%
See 1 more Smart Citation